Depositional development of the Muskeg Lake crevasse splay in the Cumberland Marshes (Canada). Issue 1 (7th October 2015) - Toonen, Willem H. J.; van Asselen, Sanneke; Stouthamer, Esther; Smith, Norman D.
Abstract: Crevasse splays are common geomorphological features in alluvial and deltaic floodplains. Although crevasse splays can develop into full avulsions, thereby transforming large areas of floodbasins, little is known about their sedimentary and geomorphological development at the decadal scale and their avulsion potential. We used aerial photography and lithological cross‐sections to reconstruct crevasse‐splay formation in the largely unmanaged floodplain of the Saskatchewan River in the Cumberland Marshes (Saskatchewan, Canada). Based on surface geomorphology and subsurface deposits, various stages of crevasse‐splay development were described which were linked to both external forcing and internal morphodynamics. Initial splay deposition, following a levee breach during a large flood, occurred as a broad but relatively thin sandy sheet in a down‐basin direction in the receiving backswamp area. In a next phase, these primary crevasse‐splay deposits blocked local down‐basin flow, thereby forcing the crevasse‐splay channel in a direction perpendicular to the parent channel and original floodbasin gradient. This created an asymmetrical splay sequence composition, which differs in appearance from more commonly observed dendritic crevasse splays. It is concluded that sedimentation patterns in the splay have been influenced by inherited effects of previously formed deposits. Feedbacks of the original floodbasin gradient and earlier stages of splay formation are suggested as prominent mechanisms in creating the current morphology, orientation, and architecture of its deposits. Copyright © 2015 John Wiley & Sons, Ltd.